On-orbit free-floating manipulation using a two-arm robotic system - Ramón, José Luis; Pomares, Jorge; Felicetti, Leonard (SciTePress - Science and Technology Publications, 2021)
A direct visual-servoing algorithm is proposed for the control of a space-based two-arm manipulator. The scenario under consideration assumes that one of the arms performs the manipulation task while the second one has an in-hand camera to observe the target zone of manipulation. The algorithm uses both the camera images and the force/torque measurements as inputs to calculate the control action to move the arms to perform a manipulation task. The algorithm integrates the multibody dynamics of the robotic system in a visual servoing framework that uses de-localized cameras. Impedance control is then used to compensate for eventual contact reactions when the end effector touches and operates the target body. Numerical results demonstrate the suitability of the proposed algorithm in specific tasks used in on-orbit servicing operations.
Keywords: Dual-Arm Manipulator; Space Robotics; On-Orbit Servicing; Visual Servoing; Impedance Control